BROADBAND SPECTROSCOPY USING TWO SUZAKU OBSERVATIONS OF THE HMXB GX 301-2 - Suchy, Slawomir; Fürst, Felix; Pottschmidt, Katja; Caballero, Isabel; Kreykenbohm, Ingo; Wilms, Jörn; Markowitz, Alex; Rothschild, Richard E. (Astrophysical Journal, 2012)
We present the analysis of two Suzaku observations of GX 301-2 at two orbital phases after the periastron passage. Variations in the column density of the line-of-sight absorber are observed, consistent with accretion from a clumpy wind. In addition to a cyclotron resonance scattering feature (CRSF), multiple fluorescence emission lines were detected in both observations. The variations in the pulse profiles and the CRSF throughout the pulse phase have a signature of a magnetic dipole field. Using a simple dipole model we calculated the expected magnetic field values for different pulse phases and were able to extract a set of geometrical angles, loosely constraining the dipole geometry in the neutron star. From the variation of the CRSF width and energy, we found a geometrical solution for the dipole, making the inclination consistent with previously published values.
Keywords: pulsars: individual (GX 301-2); stars: magnetic field; X-rays: binaries; X-rays: stars